Do oral contraceptives increase epileptic seizures?. (1st February 2017) - Reddy, Doodipala Samba
ABSTRACT: Introduction: Hormonal contraceptives are used by over 100 million people worldwide. Recently, there has been an emerging interest in studying the potential impact of oral contraceptives (OCs) on certain neurological conditions. It has been suspected for some time that hormonal birth control increases seizure activity in women with epilepsy, but there is little supportive data. Areas covered: Literature from PubMed and online sources was analyzed with respect to hormonal contraception and epilepsy or seizures. New evidence indicates that OCs can cause an increase in seizures in women with epilepsy. The epilepsy birth control registry, which surveyed women with epilepsy, found that those using hormonal contraceptives self-reported 4.5 times more seizures than those that did not use such contraceptives. A preclinical study confirmed these outcomes wherein epileptic animals given ethinyl estradiol, the primary component of OCs, had more frequent seizures that are more likely to be resistant. Expert commentary: OC pills may increase seizures in women with epilepsy and such refractory seizures are more likely to cause neuronal damage in the brain. Thus, women of child bearing age with epilepsy should consider using non-hormonal forms of birth control to avoid risks from OC pills. Additional research into the mechanisms and prospective clinical investigation are needed.